2016
DOI: 10.1186/s40779-016-0098-x
|View full text |Cite
|
Sign up to set email alerts
|

All-cause hospitalizations for inflammatory bowel diseases: Can the reason for admission provide information on inpatient resource use? A study from a large veteran affairs hospital

Abstract: BackgroundInflammatory bowel diseases (IBDs) are group of chronic inflammatory illnesses with a remitting and relapsing course that may result in appreciable morbidity and high medical costs secondary to repeated hospitalizations. The study’s objectives were to identify the reasons for hospitalization among patients with inflammatory bowel diseases, and compare inpatient courses and readmission rates for IBD-related admissions versus non-IBD-related admissions.MethodsA retrospective chart review was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 11 publications
0
15
0
1
Order By: Relevance
“…We identified 852 unique studies using our search strategy and reviewed 94 studies in detail and ultimately included 17 studies (6324 patients) in the quantitative analysis. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] The study selection flowsheet is included in Figure 1. Of these 17 studies, 7 studies were fulllength articles and 10 were abstracts.…”
Section: Resultsmentioning
confidence: 99%
“…We identified 852 unique studies using our search strategy and reviewed 94 studies in detail and ultimately included 17 studies (6324 patients) in the quantitative analysis. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] The study selection flowsheet is included in Figure 1. Of these 17 studies, 7 studies were fulllength articles and 10 were abstracts.…”
Section: Resultsmentioning
confidence: 99%
“…3,11 Although IBD is usually managed in the outpatient setting, acute flares, especially involving hemorrhage or impending bowel perforation, are life-threatening and require hospital admission. 1,11 Despite possibly requiring more resources for acuity of illness, 14 there is a minimal difference in the overall hospitalization mortality, time, or cost of weekend admissions compared with the weekdays. 6 Despite this, the weekend effect has never before been examined in this particular cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Although randomized trials in the IBD population to reduce readmissions are lacking, data from other chronic diseases have shown that the use of integrated multidisciplinary clinics to address the social and psychological burdens of chronic illness and the use of nurse case managers or “transitions coach” to improve cross-site communication, encouraging patients to take a more active role in their care by providing guidance, can reduce readmissions and improve outpatient follow-up [ 21 , 22 ]. A previous study in VA patients done by our group demonstrated that IBD patients were more likely to have significant changes in their medication profiles upon discharge from the hospital, thus highlighting the need for transitional care interventions [ 23 ].…”
Section: Discussionmentioning
confidence: 99%